INVESTIGATING FRENCH INEFFECTIVE SENTENCE CONSTRUCTION IN STUDENTS’ ACADEMIC WRITING (JURNAL DARMA AGUNG, 2023)
This study aims to explore ineffective sentence constructions in French and explain the factors that cause ineffective sentence constructions in academic writing classes in the form of students’ theses. The study employed a qualitative approach through repeated reading activities with systematic observation and recording of the phenomenon of ineffective sentence construction in the students’ theses situated at a state university in Medan, Indonesia. The research sample is five theses from 2020 to 2022 cohorts. The data for theses writing were all French sentence constructions that are ineffective in the students’ theses contained in the Introduction chapter. The findings revealed that 134 ineffective sentence constructions were as follows, (a) incomplete sentence construction as many as 34 sentences (25%), consisting of sentences that did not have a subject, predicate, and object, subject and predicate were too far apart, did not pay attention to additional information with subordination clauses, not paying attention to intra-sentence and inter-sentence conjunctions, (b) 25 (19%) incoherent sentences, consisting of word order that did not clarify the sentence, errors in the use of prepositions, errors in the use of conjunctions, (c) 28 non-parallel sentences ( 21%), caused by the construction of ideas in a serial arrangement that is not the same in form, (d) 32 (24%) illogical sentences, consisting of inappropriate word choices, the dating of certain words that make it ambiguous, and the wrong arrangement of words or phrases illogical, (e) 15 (11%) non-efficient sentences, consisting of repetition of words that have been written, repetition of subject sentences, unnecessary parsing of words, pleonasms, writing of dates, months and years that are not appropriate, and the use of words relationship that is not necessary.